Bacterial responses to background organic pollutants in the northeast subarctic Pacific Ocean. (24th June 2021) - Martinez‐Varela, Alícia; Cerro‐Gálvez, Elena; Auladell, Adrià; Sharma, Shalabh; Moran, Mary Ann; Kiene, Ronald P.; Piña, Benjamí; Dachs, Jordi; Vila‐Costa, Maria
Summary: Thousands of man‐made synthetic chemicals are released to oceans and compose the anthropogenic dissolved organic carbon (ADOC). Little is known about the effects of this chronic pollution on marine microbiome activities. In this study, we measured the pollution level at three sites in the Northeast Subarctic Pacific Ocean (NESAP) and investigated how mixtures of three model families of ADOC at different environmentally relevant concentrations affected naturally occurring marine bacterioplankton communities' structure and metabolic functioning. The offshore northernmost site (North) had the lowest concentrations of hydrocarbons, as well as organophosphate ester plasticizers, contrasting with the two other continental shelf sites, the southern coastal site (South) being the most contaminated. At North, ADOC stimulated bacterial growth and promoted an increase in the contribution of some Gammaproteobacteria groups (e.g. Alteromonadales) to the 16 rRNA pool. These groups are described as fast responders after oil spills. In contrast, minor changes in South microbiome activities were observed. Gene expression profiles at Central showed the coexistence of ADOC degradation and stress‐response strategies to cope with ADOC toxicities. These results show that marine microbial communities at three distinct domains in NESAP are influenced by background concentrations of ADOC, expanding previous assessments for polar and temperate waters.